-2/3n=22/3

Simple and best practice solution for -2/3n=22/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2/3n=22/3 equation:


n in (-oo:+oo)

(-2/3)*n = 22/3 // - 22/3

(-2/3)*n-(22/3) = 0

(-2/3)*n-22/3 = 0

-2/3*n-22/3 = 0 // + 22/3

-2/3*n = 22/3 // : -2/3

n = 22/3/(-2/3)

n = -11

n = -11

See similar equations:

| x^4-3x+20=0 | | -1/2+m=-1/2 | | 2/5n=4/15 | | b+9=33/4 | | 1/6+w=1/6 | | m-2/3=13/3 | | 1+k=17/9 | | 2/5+d=7/5 | | -28/5=w-6 | | 6+n=20/3 | | k+4=9/2 | | 17/12=b+2 | | 12=k+2 | | n-8=-26/3 | | 7+d=57/8 | | a/7-1=7 | | a+5/6=13/30 | | 73/8=w+10 | | 6b=12/5 | | 2/5+d=-1/5 | | m+7=0 | | 2/5b=2 | | -6+t=-57/11 | | 3w=-2 | | 11/9=t+5/9 | | t+9=47/5 | | 6+m=15 | | -6+m=-6 | | m+1/2=-23/2 | | 1+n=-11 | | b+6=8 | | 103/88=n+5/8 |

Equations solver categories